Improvement in plasma D-dimer level in severe SARS-CoV-2 infection can be an indicator of fibrinolysis suppression: Case reports. Issue 15 (16th April 2021) - Manzoor, Daniel; Bui, Chau; Makhoul, Elias; Luthringer, Daniel; Marchevsky, Alberto; Volod, Oksana
Abstract: Rationale: Fibrinolysis shutdown associated with severe thrombotic complications is a recently recognized syndrome that was previously seldom investigated in patients with severe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. It presents a unique therapeutic dilemma, as anticoagulation with heparin alone is insufficient to address the imbalance in fibrinolysis. And while the use of fibrinolytic agents could limit the disease severity, it is often associated with bleeding complications. There is a need for biomarkers that will guide the timely stratification of patients into those who may benefit from both anticoagulant and fibrinolytic therapies. Patient concerns: All 3 patients presented with shortness of breath along with comorbidities predisposing them to severe SARS-CoV-2 infection. One patient (Patient 3) also suffered from bilateral deep venous thrombosis. Diagnoses: All 3 patients tested positive for SARS-CoV-2 RNA by reverse transcription polymerase chain reaction (RT-PCR) and were eventually diagnosed with respiratory failure necessitating intubation. Interventions: All 3 patients required mechanical ventilation support, 2 of which also required renal replacement therapy. All 3 patients were also placed on anticoagulation therapy. Outcomes: In Patients 1 and 2, the initial D-dimer levels of 0.97 μg/ml fibrinogen equivalent units (FEU) and 0.83 μg/ml FEU were only slightly elevated (normal <0.50 μg/ml FEU). They developed rising D-dimer levels to a peak of 13.21 μg/ml FEU and >20.0 μg/ml FEU, respectively, which dropped to 1.34 μg/ml FEU 8 days later in Patient 1 and to 2.94 μg/ml on hospital day 13 in Patient 2. In Patient 3, the D-dimer level on admission was found to be elevated to >20.00 μg/ml FEU together with imaging evidence of thrombosis. And although he received therapeutic heparin infusion, he still developed pulmonary embolism (PE) and his D-dimer level declined to 5.91 μg/ml FEU. Despite "improvement" in their D-dimer levels, all 3 patients succumbed to multi-system organ failure. On postmortem examination, numerous arterial and venous thromboses of varying ages, many consisting primarily of fibrin, were identified in the lungs of all patients. Lessons: High D-dimer levels, with subsequent downtrend correlating with clinical deterioration, seems to be an indicator of fibrinolysis suppression. These findings can help form a hypothesis, as larger cohorts are necessary to demonstrate their reproducibility.